Comparison of Demographic Trends in Iran and Saudi Arabia - Valchev, Boyko (Research Papers, 2020)
This article explores how a low carbon economy transition might affect two of the leading countries in the shia/suni division in the Middle East – Iran and Saudi Arabia. The aim is to compare current and future demographic data in order to predict which of those two countries would have harder times to adapt to a low carbon economy. While comparing current demographic data, one may assume that both countries have similar characteristics, they diverge drastically when we compare the immigration statistics. Saudi Arabia is extremely dependent on immigration labour force. The analysis shows that a significant drop in its oil revenues may push those migrant away, seriously damaging its economy and the political role Saudi Arabia plays in the Middle East.
Keywords: Middle East; Immigration; Saudi arabia; Low carbon economy